2020
DOI: 10.1038/s41598-020-67403-w
|View full text |Cite
|
Sign up to set email alerts
|

Computational evidence for nonlinear feedforward modulation of fusimotor drive to antagonistic co-contracting muscles

Abstract: the sensorimotor integration during unconstrained reaching movements in the presence of variable environmental forces remains poorly understood. the objective of this study was to quantify how much the primary afferent activity of muscle spindles can contribute to shaping muscle coactivation patterns during reaching movements with complex dynamics. to achieve this objective, we designed a virtual reality task that guided healthy human participants through a set of planar reaching movements with controlled kine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…Such afferent-driven muscle activity has been shown for hindlimb extensor muscles in the cat during the stance phase of walking (Hiebert and Pearson 1999; Prochazka et al 1997a) and it likely underlies positive force feedback control and other similar types of muscle coactivation in humans (Hagbarth 1993; Prochazka et al 1997b). The afferent-driven coactivation of synergistic upper limb muscles during reaching in humans has also been suggested by simulations of primary afferent feedback and their relationships to muscle activation patterns (Hardesty et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such afferent-driven muscle activity has been shown for hindlimb extensor muscles in the cat during the stance phase of walking (Hiebert and Pearson 1999; Prochazka et al 1997a) and it likely underlies positive force feedback control and other similar types of muscle coactivation in humans (Hagbarth 1993; Prochazka et al 1997b). The afferent-driven coactivation of synergistic upper limb muscles during reaching in humans has also been suggested by simulations of primary afferent feedback and their relationships to muscle activation patterns (Hardesty et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Musculotendon lengths (i.e., muscle lengths) were calculated for each forelimb posture across the physiological range of motion in the OpenSim model using Matlab. The correlation matrix of muscle lengths across all postures was converted to heterogeneous variance explained (HVE) to emphasize agonistic relationships (Hardesty et al 2020). Hierarchical clustering was applied to HVE using the linkage function in Matlab to quantify the functional relationships between muscles.…”
Section: Hierarchical Clustering Analysismentioning
confidence: 99%
“…1A). Spherical virtual targets 8 cm in diameter were displayed in a sagittal plane and defined a set of postures and reaching tasks as described in detail in (Hardesty et al 2020) (Fig. 1B).…”
Section: Methodsmentioning
confidence: 99%
“…1B). To calculate active joint torques, we used a dynamical model similar to that used for the selection of tasks as described in (Hardesty et al 2020). The model was customized to individual morphology by scaling segment length and inertia based on individual’s height and weight using published average proportions (Winter 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that to predict patient function under novel conditions, personalized neural control models are likely to be necessary [25], and furthermore, that pre-treatment muscle synergies may facilitate the prediction of posttreatment muscle excitations [144]. While numerous studies exist that describe complex, realistic sensorimotor control models incorporating elements such as supraspinal control, modularity, central pattern generators, and proprioceptive feedback [22,[145][146][147][148][149][150][151][152][153][154][155][156][157][158][159], these models are generic rather than personalized and are typically applied to simplified planar dynamic systems. More realistic musculoskeletal models have been coupled with simpler neural control models employing modular control [25][26][27]136,137,[160][161][162][163] or proprioceptive feedback [164][165][166], but these models have yet to be evaluated in clinical treatment design scenarios.…”
Section: Prediction Of Post-treatment Function Is Difficultmentioning
confidence: 99%